Exploring the potential of synthetic and biological fungicides for managing the fungus-farming ambrosia beetle Xylosandrus compactus - Mariangela Benedetta Costanzo; Alessandro Vitale; Antonio Biondi; Giancarlo Polizzi; Antonio Gugliuzzo (PLoS ONE, 2025)
Little is known about effective control strategies targeting the invasive ambrosia beetle Xylosandrus compactus. This fungus-farming beetle is highly dependent on its primary nutritional fungal mutualist Ambrosiella xylebori. Traditionally, insect pest control programs target the pest directly. Here, we tested the potential of synthetic and microbial based fungicides to suppress the fungal mutualist, consequently hampering the beetle development. Thiophanate-methyl application to bay laurel (Laurus nobilis L.) stem sections proved to be effective in reducing the mutualist fungus occurrence in infested galleries, as well as to reduce the mean X. compactus brood size. Thiophanate-methyl and azoxystrobin significantly reduced the mean beetle brood size in extended laboratory conditions. Similarly, these two fungicides were the most effective in reducing the fungal lesion length, both when tested by soil or spray applications. Overall, thiophanate-methyl showed the highest reduction of the X. compactus brood size by spray application. No or low impact on X. compactus infestations was observed when testing the triazole mefentrifuconazole. Among tested microbial based fungicides, Trichoderma asperellum T34 was the only one causing a reduction of the fungal lesion length. To the best of our knowledge, this study provides, for the first time, baseline data on the potential of fungicides for disrupting the mutualistic interaction between X. compactus and its primary mutualist A. xylebori. These findings will help in developing novel and effective integrated pest management approaches based on the mycobiome alteration and targeting X. compactus in its invaded range.